Addition of Blood Flow Restriction in Squat Exercises to Increase the Strength of Quadriceps Muscle Groups - Arif Pristianto; Alifia Putri Latifah; Taufik Eko Susilo (Universitas Pendidikan Indonesia, 2024)
The quadriceps muscle group is important for daily activities and generating power during sports, especially sports involving the lower extremities. Squat is an effective exercise to increase the strength of the quadriceps muscle group. The Blood Flow Restriction (BFR) can increase the load during exercise leading to a significant increase in strength. The purpose of this study was to determine the effect of adding BFR in squat exercises to increase MVIC values in the quadriceps muscle group. This research was a pilot study using an experimental method with a pretest-posttest control group design. The samples of this study were 11 respondents selected using a purposive sampling technique. The samples were divided into two groups. Group 1 involved 5 respondents given a squat training with BFR, while group 2 involved 6 respondents given a squat training without BFR. The measurement of muscle strength was carried out using SEMG with the MVIC method. The result of the effect test using the paired sample t-test in group 1 obtained p-values of rectus femoris (0.018), vastus medial (0.030), and vastus lateral (0.014). The test of group 2 gained p-values of rectus femoris (0.141), vastus medial (0.034), and vastus lateral (0.04). The result of independent t-test for the different effects of the test obtained p-values of the rectus femoris (0.885), vastus medial (0.211), and vastus lateral (0.404). It concludes that squat training with BFR could significantly increase the strength of the quadriceps muscle group. Meanwhile, the squat exercise without BFR did not significantly increase the strength of the rectus femoris muscle but there was a significant muscle strength on the vastus lateral and medial muscle. There was no significant difference in the effect of squat with BFR and squat without BFR.